First report of Valsa melanodiscus causing stem canker on Arizona alder in Arizona - Wilhelmi, Nicholas (Plant disease, 2025)
Riparian forests represent a small but critically important component of the forested land in the arid Southwestern USA and Northern Mexico (Smith and Finch 2016). Arizona alder (Alnus oblongifolia) (AZ alder) is an important species in many riparian forests, providing critical ecosystem services including fixing nitrogen via association with Frankia spp., and thus representing an important source of nitrogen, directly contributing to the productivity of riparian forests (Welsh et al. 2009). In 2020, we observed elevated mortality of AZ alder (Ca. 50-60% of trees affected in some stands), prompting further investigation into causal agents. Mortality was associated with unidentified beetle activity and sunken cankers along the stem. Fruiting bodies were not observed on cankers. Isolations from canker samples on PDA yielded Cytospora-like fungal colonies with uneven growth margins and lobate appearance. Two isolates were then hyphal-tip purified in fresh PDA dishes for morphological, phylogenetic, and pathological analyses. Colonies were fast-growing, pale vinaceous with short aerial tufts giving a cottony appearance. Hyphae were hyaline to reddish, smooth, straight, branched, and septate. Pycnidia were induced on sterilized alder bark embedded in water agar for 4 weeks under a 12 to 14-h photoperiod. Conidia were allantoid, single, hyaline, aseptate, thin-walled, smooth 3.4-6 × 0.9-1.5 μm (n = 20). These morphological characteristics matched those of Valsa melanodiscus (anamorph Cytospora umbrina) (Hayova and Minter 2012). For molecular identification, genomic DNA was extracted from 2 isolates, and partial DNA sequences of the internal transcribed spacer (ITS) region of rDNA and elongation factor 1-alpha (EF-1α) gene were amplified and sequenced using primers ITS1/ITS4 (White et al., 1990) and EF1-728F/EF1-986R (Carbone and Kohn 1999). The resulting sequences of ITS (PQ894640) and TEF (PQ999094) were deposited in the GenBank. A BLASTn search of ITS and TEF sequences revealed a 98.0-100.0% of query coverage and 98.7-100.0% identity to the sequences of other Valsa melanodiscus isolates (e.g. JX438605, JX438606, JX438608, JX438619, JX438620, PQ763362) causing dieback and mortality on A. tenuifolia in Colorado and Alaska (Worrall 2009, Ruess et al. 2009). Field inoculation of 24 AZ alder tree branches (2 branches per tree) with two isolates was conducted by wounding the branch and placing a colonized agar plug over the exposed inner bark. Similarly, 10 branches were inoculated with plain agar as control. After 3 months, V. melanodiscus was cultured from 83% of the fungus-inoculated branches but not from any control branches. Most inoculated branches developed sunken elliptical cankers, while wounded control branches produced healthy callous tissue. Canker length ranged from 1.5 cm to 12.7 cm (mean: 4.3cm) in inoculated stems; branch girdling was not observed on any inoculated branches. The fungus was re-isolated from the inoculated branches and confirmed as V. melanodiscus by morphology and DNA sequencing, thus fulfilling Koch's postulates. To our knowledge, this is the first report of V. melanodiscus as a stem canker pathogen of A. oblongifolia in AZ. The disease is generally associated with hot, dry conditions. As conditions continue to become hotter and drier in the Southwest, increased incidence and impacts from this pathogen will likely be observed (Worrall 2010)